PENYULUHAN DAN IMPLEMENTASI PENGGUNAAN RIGID CUSTOM FOOT ORTHOSIS DALAM MENGURANGI DERAJAT FLATFOOT - Anggriani, Atika Febri; Utomo, Prasetyo Catur (Tahta Media Grup, 2024)
The aim of this service activity is to increase understanding about the use of rigid custom foot orthoses in reducing the degree of flatfoot in students with flat feet. Method: counseling/education regarding the effect of using rigid custom foot orthoses in reducing the degree of flat foot for teachers. After being given counseling, the teachers were guided and trained to apply the use of rigid custom foot orthoses in order to increase understanding regarding the need to use custom foot orthoses for flat foot sufferers. Then intervention was carried out in the form of providing custom foot orthoses to students who experienced flat feet. Results: more than 80% of participants understood about one of the musculoskeletal disorders of the foot, namely flat foot, more than 75% of participants were able to understand the effect of using a rigid custom foot orthosis in reducing the degree of flat foot, after follow-up for approximately 1 month several children conveyed comfortable and always using the tool, they said that the arches of his legs were starting to appear. Conclusion: outreach activities and implementation of the use of rigid custom foot orthoses in reducing the degree of flat foot can help the community in dealing with flat feet in children.